Humor in interaction - Norrick, Neal R.; Chiaro, Delia, 1953- (Pragmatics & beyond ;, 2009)
This is the first edited volume dedicated specifically to humor in interaction. It is a rich collection of essays by an international array of scholars representing various theoretical perspectives, but all concerned with interactional aspects of humor. The contributors are scholars active both in the interdisciplinary area of humor studies and in adjacent disciplines such as linguistic pragmatics, sociolinguistics, discourse analysis, psycholinguistics, gender and translation studies. The volume effectively offers an overview of the range of phenomena falling in the broad category of 'convers.